Telemedicine and Telehealth: Gaining notoriety in scientific research during the COVID-19 pandemic - Zdziarski, Alais Daiane (2022)
Background: Access to quality health services is a global challenge. However, telemedicine has been facilitating access to healthcare, especially since the advent of COVID-19. Objective: This review aimed to identify and highlight the main characteristics of research in telemedicine and telehealth, worldwide. Methods: This exploratory review employed a quantitative approach and searched the databases of Web of Science, Scopus, PubMed, SciELO, and SAGE for all fields that had the themes “telemedicine” and “telehealth” from the initial year, as per the databases, until 2020. Results: The exponential growth in research related to telemedicine and telehealth was evident; however, a substantial growth was observed in the year 2020 to provide quality care to distant places while observing safety criteria and cost-effectiveness. Moreover, thematic areas, methodologies, researchers, and university and organizational networks were also demonstrated. Conclusion: Telemedicine and telehealth enables quality healthcare access for all, even for those in remote areas, thus shortening distances between patients and health professionals.